A proteomic signature of healthspan - Chia-Ling Kuo; Peiran Liu; Gabin Drouard; Eero Vuoksimaa; Jaakko Kaprio; Miina Ollikainen; Zhiduo Chen; Luke C. Pilling; Janice L. Atkins; Richard H. Fortinsky; George A. Kuchel; Breno S. Diniz (Proceedings of the National Academy of Sciences, 2025)
The focus of aging research has shifted from increasing lifespan to enhancing healthspan to reduce the time spent living with disability. Despite significant efforts to develop biomarkers of aging, few studies have focused on biomarkers of healthspan. We developed a proteomics-based signature of healthspan [healthspan proteomic score (HPS)] using proteomic data from the Olink Explore 3072 assay in the UK Biobank Pharma Proteomics Project (53,018 individuals and 2,920 proteins). A lower HPS was associated with higher mortality risk and several age-related conditions, such as chronic obstructive pulmonary disease, diabetes, heart failure, cancer, myocardial infarction, dementia, and stroke. HPS showed superior predictive accuracy for these outcomes compared to other biological age measures. Proteins associated with HPS were enriched in hallmark pathways such as immune response, inflammation, cellular signaling, and metabolic regulation. The external validity was evaluated using the Essential Hypertension Epigenetics study with proteomic data also from the Olink Explore 3072 and complementary epigenetic data, making it a valuable tool for assessing healthspan and as a potential surrogate marker to complement existing proteomic and epigenetic biological age measures in geroscience-guided studies.